(untitled) (Transport systems and technologies, 2018)
The article noted that at this stage of development of railway transport in Ukraine, systematization of types, parameters and technical characteristics of air springs was not performed. This in turn would lead to an acceleration of their choice, depending on the tasks. In this paper, the author notes that despite the shortcomings, which include additional air flow, air springs have significant advantages compared with other elastic elements of the spring suspension. This is an opportunity to provide fairly large static deflections with simple means, and also it is necessary to damp the body oscillations. The tests of rolling stock with air spring suspension showed that despite the almost identical possibilities of helical coil springs and air springs in increasing the static deflection, the latter have vibration-proof properties and comfort. Another advantage of air springs is the possibility of perception of high horizontal and diagonal movements, vibration protection from impact of rail joints, unevenness of the track and rolling surfaces of the wheels of the wheelset, the ability to maintain a constant height of the body floor above the rail heads. As a result of the research, the types, parameters and technical characteristics of air springs, reduced models of air springs that are used on railway rolling stock were systematized. For each specific model, their static data is presented: height, volume and permissible load; change in vertical, horizontal stiffness depending on the load, the natural frequency of oscillation.